Gaya Kepemimpinan Mempengaruhi Kinerja Anggota Organisasi - I Nyoman Artayasa (Jurnal Ilmiah Cakrawarti, 2021)
Leadership Style In Organization is to know how to lead a group or organization.It can also know the influence of leadership styles used by a leader in dealing with certain situations and conditions. There are a wide range of lead styles. All of these leadership styles each have their own traits and that's what makes a leader able to lead his or her group in his or her own way that will surely aim just like a leader in general who wants to influence people to take actions that benefit the organization and itself to achieve certain goals. Whatever form his leadership style will affect the way people work as individuals or as a group.In reality leaders can influence the spirit and excitement of work, security, quality of working life and especially the level of achievement of an organization